External quality assessment for HIV rapid tests: challenges and opportunities in Haiti. Issue 6 (21st November 2018) - Jean Louis, Frantz; Excellent, Marie Lina; Anselme, Renette; Buteau, Josiane; Stanislas, Magalie; Boncy, Jacques; Domercant, Jean Wysler
Abstract : HIV rapid diagnostic tests (RDTs) are instrumental in scaling-up HIV testing services (HTS) in low-income and middle-income countries (LMICs). HIV misdiagnosis is a growing concern in the era of expanded and decentralised access to HTS. External quality assurance (EQA) programme including proficiency testing (PT) for HIV RDTs is a priority to guarantee the accuracy and reliability of the patients' result. Here we are sharing Haiti's 11 years' experience in implementing HIV RDTs EQA programme to help address some of the challenges faced by other LMICs. HTS is expanding beyond laboratory walls and HIV RDTs are increasingly performed by non-laboratory personnel and closer to the community. EQA programmes for HIV RDTs in Haiti have faced significant challenges. In expanded HTS settings, non-laboratory personnel (nurses, aid-nurses) involved in HIV RDT are usually undertrained and participate poorly in PT programs. In more than half of the lab enrolled in the PT programme in Haiti, the panels are always tested by the most experienced technician, defying the purpose of the program which is to evaluate the performance of the technician performing the test daily. EQA programme in Haiti and other LMICs are usually not tailored to address community HIV testing challenges. With decreased funding and absence of government financial commitment to HIV RDTs EQA programmes, more innovative and cost-efficient strategies are sought to ensure the quality of HIV diagnosis in LMICs. Qualified human resources, continuous training, supervision and community-tailored PT programmes remain key components for the success of HIV RDT quality management.